Pengaruh Pendidikan Perawatan Bayi Baru Lahir dengan Metode Syndicate Group terhadap Pengetahuan Kader Posyandu di Desa Sumberdanti Wilayah Kerja Puskesmas Sukowono Kabupaten Jember (The Effect of Newborn Care Education Using Syndicate Group Method to the - Rizqi Fauziyah Rofif; Hanny Rasni; Lantin Sulistyorini (Pustaka Kesehatan, 2016)
Newborn (BBL) has a high risk of mortality. It happened because the public’s knowledge and practiceabout simple treatments such as prevention of hypothermia, giving colostrum and exclusivebreastfeeding is still very poor. Cadre is one closest person of newborn‘s mother who can affectmaternal behavior, so she can provides a good information to newborn‘s mothers and families whenher knowledge has been good. The aim of this research is to obtain information from the analysis ofthe effect in newborn care education by Syndicate Group methods on cadres’ knowledge inSumberdanti village. This research used pre-experimental method with one group pretest-post testdesign that used 24 cadres’ of Sumberdanti Village who registered by the village midwife. Beforegetting intervention, there were 50% cadres who belong to category of having enough knowledgeand there were 58.3% cadres who belong to the category of having good knowledge after gettingintervention. Analysis of hypothesis used Wilcoxon Signed Rank test with α = 0.05 which obtained pvalue = 0.001, indicating a significant effect of newborn care education by Syndicate Group methodon cadres’ knowledge. Hopefully, the Sukowono Public Health Center and the midwives can continueimproving the cadres’ knowledge by interactive methods such as Syndicate Group and othermethods, so that their role can be more optimal.Keywords: Posyandu Cadres, Knowledge Of Newborn Care, Syndicate Group Method